Studi Komparatif Keanekaragaman Gastropoda pada Sungai Perkotaan dan Sungai Pedesaan di Kabupaten Klaten (Studi Kasus Kecamatan Klaten Tengah dan Kecamatan Juwiring): Penelitian - Rahmad Renaldi, Dian; Alifia Tsurayya, Davina; Gemilang, Syahrul (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the differences in gastropod diversity between urban and rural rivers in Klaten as an indicator of environmental quality. Data were collected through field surveys, measurements of physico-chemical parameters, and species identification. The Shannon–Wiener index was used to assess community variation and its relationship with water conditions. The results show that gastropod abundance was considerably higher in rural areas (214 individuals) than in urban areas (87 individuals). Diversity was also higher in rural rivers with an H’ value of 0,79 compared to 0,62 in urban rivers. Dominance index values indicate unstable community structures, with C values of 0,64 in rural sites and 0,71 in urban sites, suggesting the presence of a strongly dominant species. Physico-chemical parameters explain these differences: rural rivers had pH 6.6, turbidity 22 NTU, temperature 27.8°C, and DO 5.4 mg/L, which support higher species richness. In contrast, urban rivers showed pH 5.8, turbidity 56 NTU, temperature 29.4°C, and DO 3.1 mg/L, indicating more polluted conditions. These conditions reduced diversity, limited sensitive species, and increased dominance of tolerant species, resulting in a less balanced community structure.